A FERTILE SOIL? Indonesia and Islamic Fundamentalism (State Islamic University (UIN) of Sunan Ampel Surabaya, 2007)
BOOK REVIEW:Book title:Joining the caravan? The Middle east, Islamism and IndonesiaAuthor:Anthony Bubalo and Greg FealyNo. of Pages:xxii + 128Year:2005Publisher:Lowy Institute for International Policy, SydneyWebsite:http://www.lowyinstitute.org/PublicationGet.asp?i=229